The impact of diversified farming practices on terrestrial biodiversity outcomes and agricultural yield worldwide: A systematic review protocol - Sánchez, Andrea C.; Estrada-Carmona, Natalia; Juventia, Stella D.; Jones, Sarah K. (MDPI, 2021)
The expansion and intensification of agriculture have led to global declines in biodiversity. This paper presents a systematic review protocol to clarify under what management and landscape contexts diversified farming practices are effective at improving outcomes for terrestrial biodiversity, and potential trade-offs or synergies with agricultural yields. The systematic review will be developed following the Reporting Standards for Systematic Evidence Syntheses (ROSES). The review will include articles that compare levels of diversity (e.g., abundance, richness, Shannon’s diversity index) of any terrestrial taxon (e.g., arthropods, mammals) in diversified farming systems to levels in simplified farming systems and/or natural habitats, prioritising articles that also report agricultural yields. We will search for relevant peer-reviewed primary studies in two global repositories: Scopus andWeb of Science, and among primary studies included in previous meta-analyses that are retrieved from the search. Full-texts of identified articles will be screened using a clear inclusion/exclusion eligibility criteria. All included articles will be assessed to determine their internal validity. A narrative synthesis will be performed to summarize, describe and present the results, and where the articles provide sufficient and appropriate data, we will conduct a quantitative meta-analysis.